Penanaman Pohon dengan Sistem Gugur Gunung sebagai Gerakan Merawat Lingkungan dan Sosial Kemasyarakatan di Koripan 1 Dlingo Bantul - Ichsan, Ahmad Shofiyuddin; Niat, Khoirun; Abdullah, Muhammad Ayub; Masakin, Muhammad Irham; Khairunnas, Muhammad; Fakhrurrozi, Muhammad Arya; Alayya, Almas Angeli Rahma; Isyanti, Amalia Putri; Khairani, Anis; Dewi, Anggi Pascalia; Isnaini, Dewi Lailatul; Ulhaq, Dhiya; Hasanah, Latifa Nur (LP3M IAIFA Kediri, 2025)
This service aims to reveal the tree planting movement with the Gugur Gunung system in order to care for the environment and social community in Koripan 1 Dlingo Bantul Yogyakarta. The service providers used participatory methods by emphasizing the full involvement of the community and service providers in the activity program. The service results showed that tree planting was carried out in two places, namely in Sendang Kali Deso by planting fruit trees and at the Situs Petilasan Gunung Pasar by planting ornamental trees. This program was carried out by all elements of the community with three stages of activities, namely formal opening, symbolic handover of tree seedlings by relevant figures and stakeholders, and finally the implementation of planting at the service location. With the implementation of a program based on the Gugur Gunung system, the community and community servants believe that this activity has many functions and benefits for themselves, their social life, and future generations of the community.